1934
DOI: 10.1172/jci100602
|View full text |Cite
|
Sign up to set email alerts
|

Passage of Native Proteins Through the Normal Gastro-Intestinal Wall 1

Abstract: The view most generally held to-day by the physiologist, chemist and clinician is that undigested antigens are not absorbed through the normal gastro-intestinal wall; and that when such absorption does occur, it is because abnormal or pathological conditions exist, such as stasis, the excessive flooding of the intestines with protein foods, lessened activity of the digestive enzymes, altered conditions of the intestinal mucosa, and greater permeability of the intestinal wall characteristic of new-borns and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1935
1935
1984
1984

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Such reactions have been passively transferred by the intracutaneous injection of serum from an allergic individual into the skin of a normal recipient followed by the local injection 24 hours later of the food antigen to which the donor is sensitive (57). Similar local reactions have been reported when the food antigen was administered orally 24 hours after injection of serum into the skin (59). Local reactions similar to those that followed mast cell degranulation in human skin have been reported in vivo after passive sensitization of human ileum and colonic mucosa (34).…”
Section: Etiology and Pathogenesissupporting
confidence: 64%
“…Such reactions have been passively transferred by the intracutaneous injection of serum from an allergic individual into the skin of a normal recipient followed by the local injection 24 hours later of the food antigen to which the donor is sensitive (57). Similar local reactions have been reported when the food antigen was administered orally 24 hours after injection of serum into the skin (59). Local reactions similar to those that followed mast cell degranulation in human skin have been reported in vivo after passive sensitization of human ileum and colonic mucosa (34).…”
Section: Etiology and Pathogenesissupporting
confidence: 64%
“…Systemic signs suggest that nematode materials are absorbed from the gut into the body, or cause a reaction in the gut which liberates pharmocologic materials. There is evidence that large molecules-including protein-will under certain conditions cross the gut and enter the body of the adult animal (milk protein, horse serum, egg albumin in guinea pigs, Ratner and Gruehl, 1934;Hartley, 1942; diphtheria antitoxin in sheep, Bullen and Batty, 1957;bacterial endotoxin, Ravin and Fine, 1962). Symons and Fairbairn (1962) have shown that Nippostrongylus brasiliensis causes anatomical changes of the gut surface and alteration of certain transport and absorption mechanisms of the gut of infected rats.…”
Section: Discussionmentioning
confidence: 99%
“…The permeability of the intestine For allergic reactions to food protein to be initiated one expects that allergen enters the blood stream or at least penetrates the intestinal epithelium and lamina propria which is so rich in immunologically competent cells. The permeability of the gastrointestinal tract has occupied research workers for about 90 years and the early literature is well reviewed by Ratner & Gruehl (1934). The first experiments in this field employed one of three methods:…”
Section: Aetiologieal Eonsiderationsmentioning
confidence: 99%